SPing: a user‐centred debugging mechanism for software defined networks. Issue 2 (1st March 2017) - Tseng, Fan‐Hsun; Chang, Kai‐Di; Liao, Shang‐Chuan; Chao, Han‐Chieh; Leung, Victor C.M.
Abstract : Software defined networking (SDN) paradigm currently does not integrate with any debugging or diagnosing mechanism. Services through Internet connection may not work properly due to network problems, such as loop and black hole problems. The study introduces sPing, a user‐centred debugging mechanism for users debugging and troubleshooting network problems in SDN. The sPing diagnoses problems in data plane by collecting and recording specific packets based on programmable capability. It not only detects network loop and black hole but also discovers the hidden information of data link layer. The discovery of layer 2 information is unachievable to existing SDN‐based debuggers. The authors experiment the sPing on three different brands of SDN switches for verifying its proof of concept, and simulate it in the Mininet emulator for evaluating its performance. Results showed that the proposed sPing mechanism assists SDN users in debugging network problems and in maintaining network functionalities.